School Belonging, Generational Status, and Socioeconomic Effects on Mexican‐Origin Children's Later Academic Competence and Expectations. (8th December 2014) - Hernández, Maciel M.; Robins, Richard W.; Widaman, Keith F.; Conger, Rand D.
Abstract : This study examined factors that relate to academic competence and expectations from elementary to middle school for 674 fifth‐grade students (50% boys; M age  = 10.86 years) of Mexican origin. Models predicting academic competence and expectations were estimated using a structural equation modeling (SEM) framework, with longitudinal data from fifth to eighth grades. School belonging (i.e., social and emotional connectedness to school) predicted greater academic competence and expectations over time. Findings indicate that student feelings of belonging in school may act as a resource that promotes academic competence and expectations. Furthermore, family income, parent education, and generational status had direct effects on academic competence and expectations to some degree, suggesting the importance of contextual factors in this process.